Shopping for Health: Breakfast Cereals - Jenna Seckar; Wendy J. Dahl (EDIS)
It is no secret that breakfast is an important meal. Eating breakfast provides you with physical and mental energy to start the day, along with vitamins and minerals. Cereal is a quick, versatile, and budget-friendly breakfast choice. The benefits of eating a healthy cereal include increased fiber intake and lower body weight. But navigating the cereal aisle at your local grocery store can be an overwhelming experience. Continue reading this 3-page fact sheet to learn more about cereal and how to find your new go-to breakfast choices. Written by Jenna Sechar and Wendy J. Dahl, and published by the Food Science and Human Nutrition Department, December 2015.